KOMUNIKASI TRANSENDENTAL MASYARAKAT ADAT BUTON DALAM MENGEKSPRESIKAN RASA SYUKUR PANEN RAYA TAHUNAN: (STUDI ETNOGRAFI TERHADAP BUDAYA TUTURA SIOTAPINA BUTON) - Alamsyah, Alamsyah (KOMUNIKATA57, 2020)
The aims of study are to find out the historical relations of tutura Siotapina, the implementation process, the meaning behind it, the transcendental communication in it, and the potential of tourist destination. The subject is the traditional community of Wasuamba as the main.By using descriptive qualitative method and participatory observation data in the ethnographic paradigm of communication, the conclusions are obtained:The meanings of tutura Siotapina are the harmonization with God, others and nature. The core message is forest conservation with all its historical values.Transcendental communication is from the message of ancestral spirit, a message to continue in preserving the forest as the key to prosperity. Transcendental communication is a human consciousness as a real self (full of limitations), symbolic (cultural) and imaginary (imagination of the Almighty).